PENGEMBANGAN MODUL PEMROGRAMAN WEBSITE CONTENT MANAGEMENT SYSTEM UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PENGELOLAAN WEBSITE SEKOLAH SMA NEGERI 1 CEPOGO BOYOLALI - Putri Utami; Dian Hidayati (Academy of Education Journal, 2021)
The development and advancement of science and technology can provide effectiveness and interactivity in the world of education. The school website is a technology product that must be used by schools. This study aims to develop and determine the feasibility of a website programming module to improve teachers' abilities in managing school websites. This research is a Research and Development (RnD) development research using the ADDIE development method. Data collection techniques using interviews and questionnaires then analysed using qualitative and quantitative data. The subjects of this study were media experts, teachers and operators at SMA Negeri 1 Cepogo. The results of this study indicate that research and development have carried out using the ADDIE model steps, namely (Analysis, Design, Development, Implementation, Evaluation). The average assessment by the score expert validation test obtained was 87.1 included in the "Very Good" category, the response of the phase 1 field test teacher and stage 2 field test obtained an average value of 81.8 in the "Very Good" category. The quantitative data analysis took the average results of the assessment of expert validation tests and user trials. The score is 84.45 with the category "Very Good" and shows that the website programming module is suitable for use by teachers in managing school websites.